Books
in black and white
Main menu
Share a book About us Home
Books
Biology Business Chemistry Computers Culture Economics Fiction Games Guide History Management Mathematical Medicine Mental Fitnes Physics Psychology Scince Sport Technics
Ads

Elementary differential equations 7th edition - Boyce W.E

Boyce W.E Elementary differential equations 7th edition - Wiley publishing , 2001. - 1310 p.
ISBN 0-471-31999-6
Download (direct link): elementarydifferentialequat2001.pdf
Previous << 1 .. 381 382 383 384 385 386 < 387 > 388 389 390 391 392 393 .. 486 >> Next

n2n2 2
28c.
28d. The maximum error does not approach zero in either case, due to Gibb's phenomenon. Note that the coefficients in both series behave like 1/n as n ^ ^ since there is an n in the numerator.
31. We have |L f(x)dx = J
f(x)dx + I Lf(x)dx. Now, if we let
-L JO
y in the first integral on the right, then
f(x)dx
f(x)dx
= JL0
= -Jo
0f(-y)(-dy) = JLf(-y)dy
o
Lf(y)dy + JLf(x)dx
0
= -Jo
f(y)dy. Thus
0.
a
n
32. To prove property 2 let f1 and f2 be odd functions and let f(x) = f1(x) f2(x). Then f(-x) = f1(-x) f2(-x) =
-f1(x) [-f2(x)] = -f1(x) + f2(x) = -f(x), so f(x) is
odd. Now let g(x)= f1(x)f2(x), then g(-x) = f1(-x)f2(-x) = [-f1(x)][-f2(x)] = f1(x)f2(x) = g(x)
and thus g(x) is even. Finally, let h(x) = f1(x)/f2(x) and hence h(-x) = f1(-x)/f2(-x) = [-f1(x)]/[-f2(x)] =
f1(x)/f2(x) = h(x), which says h(x) is also even.
Property 3 is proven in a similar manner.
216
Section 10.4
34. Since F(x) = xf(t)dt we have Jo
F(-x) = f(t)dt = - f(-s)ds by letting t = -s. If f Jo Jo
is an even function, f(-s) = f(s), we then have
F(-x) = - xf(s)ds = -F(x) from the original definition of Jo
F. Thus F(x) is an odd function. The argument is similar if f is odd.
35. Set x = L/2 in Eq.(6) of Section 10.3. Since we know f
is continuous at L/2, we may conclude, by the Fourier
theorem, that the series will converge to
f(L/2) = L at this point. Thus we have
L = L/2 + (2L/n) ^ (-1) n+1/(2n-1), since
n=1
n+1
sin[(2n-1)n/2] = (-1)n+. Dividing by L and simplifying
-V-, , 1 CO __
(-1) n+1 V1 (-1)n
. n n n V (-1) v
yields = 7 ------- = 7 -
4 ^(2-1) ^
4 ' (2n-1) ' 2n+1
n=1 n=0
37a. Multiplying both sides of the equation by f(x) and integrating from 0 to L gives
L[f(x)]2dx = I L[f(x) 7 bnsin(nnx/L)]dx
JoL[f(x)] 2dx = |L[f(x) 71
n=1
CO CO
= bnJLf(x)sin(nnx/L)dx = (L/2) bnn, by Eq.(8).
n=1 n=1
This result is identical to that of Problem 17 of Section
10.3 if we set an = 0, n = 0,1,2,... , since 1 L 2 2 L 2
[f(x)]2dx = [f(x)]2dx . In a similar manner, it
L -L L 0
can be shown that
CO
(2/L)|L[f(x) ] 2dx = a2/2 + 7an.
n=1
37b. Since f(x) = x and bn = 2L(-1) n+1/nn (from Eq.(9)), we
n
obtain
CO
(2/L)JL[f(x)]2dx = (2/L)JLx2dx = 2L2/3 =
bn =
n=1
74L2/n2n2 = 4L2/n2 7 d/n2) or n2/6 = 7 (1/n2).
n=1 n=1 n=1
Section 10.5
217
We assume that the extensions of f and f' are piecewise continuous on [-2L,2L]. Since f is an odd periodic function of fundamental period 4L it follows from properties 2 and 3 that f(x)cos(nnx/2L) is odd and f(x)sin(nnx/2L) is even. Thus the Fourier coefficients of f are given by Eqs.(8) with L replaced by 2L; that is an = 0, n = 0,1,2,... and
bn = (2/2L)I2Lf(x)sin(nnx/2L)dx, n = 1,2,... . The
Jo
Fourier sine series for f is f(x) =
bnsin(nnx/2L).
n=1
39. From Problem 38 we have bn = (1/L) 2Lf(x)sin(nnx/2L)dx
Jo
= (1/L)ILf(x)sin(nnx/2L)dx + (1/L)I2Lf(2L-x)sin(nnx/2L)dx Jo Jl
= (1/L) ILf(x)sin(nnx/2L)dx - (1/L) I0f(s)sin[nn(2L -s)/2L]ds Jo Jl
= (1/L)ILf(x)sin(nnx/2L)dx-(1/L)ILf(s)cos(nn)sin(nns/2L)ds
00
and thus bn = 0 for n even and
bn = (2/LH Lf(x)sin(nnx/2L)dx for n odd. The Fourier 0
series for f is given in Problem 38, where the bn are given above.
Section 10.5, Page 579
3. We seek solutions of the form u(x,t) = X(x)T(t).
Substituting into the P.D.E. yields X"T + X'T' + XT' =
X"T + (X' + X)T' = 0. Formally dividing by the quantity
(X' + X)T gives the equation X"/(X' + X) = -T'/T in which
the variables are separated. In order for this equation to be valid on the domain of u it is necessary that both sides be equal to the same constant X. Hence
X"/(X' + X) = -T'/T = X or equivalently,
X" - X(X' + X) = 0 and T' + XT = 0.
5. We seek solutions of the form u(x,y) = X(x)Y(y).
Substituting into the P.D.E. yields X"Y + (x+y)XY" =
X"Y + xXY" + yXY" = 0. Formally dividing by XY yields X"/X + xY"/Y + yY"/Y = 0. From this equation we see that the presence of the independent variable x multiplying the term uyy in the original equation leads to the term xY"/Y when we attempt to separate the variables. It follows that the argument for a separation constant does not carry through and we cannot replace the P.D.E. by two
O.D.E.
218
Section 10.5
8. Following the procedures of Eqs.(5) through (8), we set u(x,y) = X(x)T(t) in the P.D.E. to obtain X"T = 4XT', or x"x = 4T'/T, which must be a constant. As stated in the text this separation constant must be -X2 (we choose -X2 so that when a square root is used later, the symbols are simpler) and thus X" + X 2X = 0 and T + (X 2/4)T = 0. Now u(0,t) = X(0)T(t) = 0, for all t > 0, yields X(0) = 0, as discussed after Eq.(11) and similarly u(2,t) = X(2)T(t) = 0, for all t > 0, implies X(2) = 0. The D.E. for X has the solution X(x) = CicosXx + C2sinXx and X(0) = 0 yields Ci = 0. Setting x = 2 in the remaining form of X yields X(2) = C2sin2X = 0, which has the solutions 2X = nn or X = nn/2, n = 1,2,... .
Note that we exclude n = 0 since then X = 0 would yield
X(x) = 0, which is unacceptable. Hence
Previous << 1 .. 381 382 383 384 385 386 < 387 > 388 389 390 391 392 393 .. 486 >> Next